A block to pre-prepared movement in gait freezing, relieved by pedunculopontine nucleus stimulation. - Thevathasan, W; Pogosyan, A; Hyam, J; Jenkinson, N; Bogdanovic, M; Coyne, T; Silburn, P; Aziz, T; Brown, P (2011)
Gait freezing and postural instability are disabling features of Parkinsonian disorders, treatable with pedunculopontine nucleus stimulation. Both features are considered deficits of proximal and axial musculature, innervated predominantly by reticulospinal pathways and tend to manifest when gait and posture require adjustment. Adjustments to gait and posture are amenable to pre-preparation and rapid triggered release. Experimentally, such accelerated release can be elicited by loud auditory stimuli--a phenomenon known as 'StartReact'. We observed StartReact in healthy and Parkinsonian controls. However, StartReact was absent in Parkinsonian patients with severe gait freezing and postural instability. Pedunculopontine nucleus stimulation restored StartReact proximally and proximal reaction times to loud stimuli correlated with gait and postural disturbance. These findings suggest a relative block to triggered, pre-prepared movement in gait freezing and postural instability, relieved by pedunculopontine nucleus stimulation.